2016
DOI: 10.1007/978-3-319-31232-3_9
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Relevancy Detection: Contributions to the Automatic Detection of Relevance in Social Networks

Abstract: In this paper we analyze the information propagated through three social networks. Previous research has shown that most of the messages posted on Twitter are truthful, but the service is also used to spread misinformation and false rumors. In this paper we focus on the search for automatic methods for assessing the relevance of a given set of posts. We first retrieved from social networks, posts related to trending topics. Then, we categorize them as being news or as being conversational messages, and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Considering the full feature set, MinDist achieved the best precision (0.72) while RF got the best accuracy (0.64), recall (0.78), F 1 (0.71), AUC (0.78) and AP (0.62). Although using a different dataset, these numbers already show better results than Figueira et al (2016), who achieved an accuracy of 0.59 and F 1 of 0.68.…”
Section: Initial Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Considering the full feature set, MinDist achieved the best precision (0.72) while RF got the best accuracy (0.64), recall (0.78), F 1 (0.71), AUC (0.78) and AP (0.62). Although using a different dataset, these numbers already show better results than Figueira et al (2016), who achieved an accuracy of 0.59 and F 1 of 0.68.…”
Section: Initial Resultsmentioning
confidence: 84%
“…The obtained results show a substantial improvement towards the only known work that tackled the same problem (Figueira et al, 2016), but where a much simpler feature set was exploited and a smaller dataset was used, to reach an accuracy of 0.59 and a F 1 of 0.68. Because of the different datasets used and, especially, the different classification goals and target classes, no deeper comparison can be made with related work, apart from a shallow analysis on the performance numbers reported.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Because they provided obvious context and were at the epicenter of our study, the following words were removed from the clouds shown in Figure 2: "Roy," "Moore," and "Alabama." These word clouds illustrate important context for understanding the discourse and rhetoric [36] within each time period (see Section 3.2 for descriptions of the Events and the Time Periods).…”
Section: News Sources and News Storiesmentioning
confidence: 99%